KETERDAPATAN INTAN SEKUNDER DI SEPANJANG SUNGAI LANDAK, KALIMANTAN BARAT - Aziz, Said (Pusat Survei Geologi, 2007)
Alluvial diamonds are found in several places in Kalimantan, out up to now the source (rock) of alluvial diamond in Kalimantan is not known yet. Since 19th centuries, some companies had explored alluvial diamond in these areas but none of them have succeded to find the source rock of alluvial diamond.The study of alluvial diamond distribution in West Kalimantan, especially along Landak River, indicates that the alluvial diamond in this area is limited only in Protolandak drainages, including Landak and Sekayam River regions.The result of heavy mineral analysis from this study could be used to estimate the distribution of alluvial diamond and heavy minerals content in this area. Besides this, it is also used to trace where the source rock of alluvial diamond comes from. Keywords.: alluvial diamond, heavy mineral, West Kalimantan